Active suspension of a full car model using fuzzy reasoning based on single input rule modules with dynamic absorbers. (1st January 2003) - Yoshimura, T.; Watanabe, K.
This paper presents an active suspension system of a full car model using fuzzy reasoning with dynamic absorbers. It is assumed that the full car model moves with the constant speed by a steering angle and is subject to excitation from an irregular road. The active controls at the suspension locations are respectively constructed as a weighted sum of the defuzzificated values of the outputs using fuzzy reasoning based on single input rule modules. The dynamic absorbers fitted to the wheel axles are designed to reduce the suspension and tyre deflections. The simulation result indicates that the proposed active suspension system is very effective in the performance of vibration isolation.